δPKC inhibition or εPKC activation repairs endothelial vascular dysfunction by regulating eNOS post-translational modification - Monti, Martina (2009)
The balance between endothelial nitric oxide synthase (eNOS)-derived nitric oxide (NO) and reactive oxygen species (ROS) production determines endothelial-mediated vascular homeostasis. Activation of protein kinase C (PKC) has been linked to imbalance of the eNOS/ROS system, which leads to endothelial dysfunction. We previously found that selective inhibition of delta PKC (δPKC) or selective activation of epsilon PKC (εPKC) reduces oxidative damage in the heart following myocardial infarction. In this study we determined the effect of these PKC isozymes in the survival of coronary endothelial cells (CVEC). We demonstrate here that serum deprivation of CVEC increased eNOS-mediated ROS levels, activated caspase-3, reduced Akt phosphorylation and cell number. Treatment with either the δPKC inhibitor, δV1-1, or the εPKC activator, ψεRACK, inhibited these effects, restoring cell survival through inhibition of eNOS activity. The decrease in eNOS activity coincided with specific de-phosphorylation of eNOS at Ser1179, and eNOS phosphorylation at Thr497 and Ser116. Furthermore, δV1-1 or ψεRACK induced physical association of eNOS with caveolin-1, an additional marker of eNOS inhibition, and restored Akt activation by inhibiting its nitration. Together our data demonstrate that 1) in endothelial dysfunction, ROS and reactive nitrogen species (RNS) formation result from uncontrolled eNOS activity mediated by activation of δPKC or inhibition of εPKC 2) inhibition of δPKC or activation of εePKC correct the perturbed phosphorylation state of eNOS, thus increasing cell survival. Since endothelial health ensures better tissue perfusion and oxygenation, treatment with a δPKC inhibitor and/or an εPKC activator in diseases of endothelial dysfunction should be considered.